EDUCATION IN ORAL HEALTH: A Reflective Approach for Quality of Life. - Mendes Sá , Antonio Carlos (Brazilian Journal of Implantology and Health Sciences, 2020)
This work aims at critical reflection on the actions that determine a good level of oral health. Health promotion is a process that can positively affect the quality of life of a population. Dental problems have a low priority compared to diseases considered to be of social relevance. Prevention of oral diseases must be developed at three levels: primary, secondary and tertiary. Self-diagnosis is extremely important, because the sooner the problem is detected and prevention services are activated, the greater the chances of an effective treatment. Among oral health problems, dental caries is considered a damage that deserves higher priority due to its high prevalence. Oral cancer gained the second degree of priority, due to its severity, followed by periodontal diseases. Education in oral health has been increasingly required, taking into account the low cost and the possibilities of dental impact on public health. Therefore, the role of educating should not be the exclusive responsibility of the professional conventionally called teacher, but of any citizen.